Norcantharidin overcomes vemurafenib resistance in melanoma by inhibiting pentose phosphate pathway and lipogenesis via downregulating the mTOR pathway - Wang, Lei; Otkur, Wuxiyar; Wang, Aman; Wang, Wen; Lyu, Yitong; Fang, Lei; Shan, Xiu; Song, Mingzhou; Feng, Yan; Zhao, Yi; Piao, Hai-Long; Qi, Huan; et al. (Frontiers in Pharmacology, 2022)
Melanoma is the most aggressive type of skin cancer with high incidence and low survival rate. More than half of melanomas present the activating BRAF mutations, along which V600E mutant represents 70-90%. Vemurafenib (Vem) is an FDA-approved small-molecule kinase inhibitor that selectively targets activated BRAF V600E and inhibits its activity. However, majority of patients treated with Vem develop acquired resistance. Hence, this study aims to explore a new treatment strategy to overcome the Vem-resistance. Here, we found that a potential anti-cancer drug norcantharidin (NCTD) displayed more significant proliferation inhibitory effect against Vem-resistant melanoma cells (A375R) than the parental melanoma cells (A375), which promised to be a therapeutic agent against BRAF V600E mutant and acquired Vem-resistant melanoma. Metabolomics analysis showed that NCTD could specially reverse the upregulation of pentose phosphate pathway and lipogenesis resulted from Vem-resistance. In addition, transcriptomic analysis showed a dramatical downregulation in genes which related to lipid metabolism and mammalian target of rapamycin (mTOR) signaling pathway in A375R cells, but not in A375 cells, upon NCTD treatment. Moreover, NCTD upregulated Butyrophilin (BTN) family genes, which played important roles in modulating T cell response. Consistently, we found Vem-resistance led to an obvious elevation of p-mTOR expression, which could be remarkably reduced by NCTD treatment. Taken together, NCTD may serve as a promising therapeutic option to resolve the problem of Vem-resistance and to improve patient outcomes by combining with immunomodulatory therapy.